ANALISIS DAN PENGEMBANGAN TEMPAT SAMPAH CERDAS DENGAN PENDEKATAN ADDIE - Christopher Khomali; Muhamad Dody Firmansyah (P3M Institut Teknologi Pagar Alam, 2023)
This research is a design research which aims to produce a smart trash bin using Arduino Uno with a microcontroller design system. This research consists of two stages, namely hardware design and continued with software design using the C language which consists of making the main program and the controlling program and the data obtained will later be uploaded via the Arduino IDE. The method in this research is Research and Development (R&D). The results of this research itself is a prototype of a smart trash can design that provides notifications via the website. The trials carried out on this smart trash bin were in the form of testing supporting components, namely ultrasonic/distance sensors and testing the system as a whole. The results of this trial function properly as evidenced by the ability of the system to provide notification that the trash can is full through the website.